Perencanaan Control Valve Pada Head Tank PLTA Tulungagung Menggunakan PLC - Hidayat, Mohammad Noor; Nursal, Elan Causa; Ronilaya, Ferdian; Muhammad Fahmi Hakim (Elposys: Jurnal Sistem Kelistrikan, 2023)
Head Tank of the Tulungagung Hydro Electric Power Plan of PT PJBUP Brantas still has a manual control valve which consists of  a gate valve and a pair of  float valves. There are some problems when the pipe of the float valve is blocked by cediment and debris, it could affect the cooling water system and make damage to the power plant. In this research, there would build a plan of the automatic control valve of the Tulungagung HEPP. PLC Siemens Simatic Step 7 was used as a control base on a SCADA software Wonderware Intouch version 10.0.0. In this modification plan, a pair of float valve changed over solenoid valve and manual gate valve change over motorized valve. For the water level that would be ultrasonic sensor SICK UM 30 as a input for the power meter Omron Procces Meter K3MA-J. The reliability of this modification are excellence and complete for the auto/manual control even for the long distance one. Moreover this modification also has excellence safety.